1993
DOI: 10.1111/j.1432-1033.1993.tb18013.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatocytic autophagy by okadaic acid and other protein phosphatase inhibitors

Abstract: Autophagy, measured as the sequestration of electroinjected [3H]raffinose or endogenous lactate dehydrogenase, was inhibited in isolated rat hepatocytes by the protein phosphatase inhibitors okadaic acid, calyculin A and microcystin-LR. Okadaic acid, the most potent inhibitor, suppressed autophagy almost completely at 15 nM, suggesting inhibition of a protein phosphatase of type 2A. Okadaic acid had no effect on ATP levels, protein synthesis or cellular viability at this concentration, but caused a disruption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 63 publications
6
54
0
Order By: Relevance
“…for example the inhibition of the mitogen-activated protein kinase kinases MEK1 and MEK2 by PD-98059 (5Ј-methoxy-6Ј-aminoflavone) (69), and of cyclin-dependent protein kinases by flavopiridol (70)). The okadaic acid-antagonistic effect of naringin on hepatocytic autophagy can be mimicked by several inhibitors of CaMK-II (71,72), but as shown in the present study, naringin had no direct inhibitory effect on CaMK-II; nor did it affect PKA or PKC activity in in vitro assays. 2 However, by using a proteomic approach in combination with phosphospecific immunoblotting, we were able to identify a number of naringin-sensitive protein phosphorylations in intact hepatocytes.…”
Section: Table III Protective Effects Of Protein Kinase Inhibitors Agmentioning
confidence: 57%
See 1 more Smart Citation
“…for example the inhibition of the mitogen-activated protein kinase kinases MEK1 and MEK2 by PD-98059 (5Ј-methoxy-6Ј-aminoflavone) (69), and of cyclin-dependent protein kinases by flavopiridol (70)). The okadaic acid-antagonistic effect of naringin on hepatocytic autophagy can be mimicked by several inhibitors of CaMK-II (71,72), but as shown in the present study, naringin had no direct inhibitory effect on CaMK-II; nor did it affect PKA or PKC activity in in vitro assays. 2 However, by using a proteomic approach in combination with phosphospecific immunoblotting, we were able to identify a number of naringin-sensitive protein phosphorylations in intact hepatocytes.…”
Section: Table III Protective Effects Of Protein Kinase Inhibitors Agmentioning
confidence: 57%
“…The toxins examined in the present study differ in their absolute as well as their relative potencies toward PP1 and PP2A, yet all of them induced plectin phosphorylation as well as fragmentation of the plectin network. Okadaic acid is readily taken up by isolated hepatocytes (72), and its high absolute potency with regard to plectin phosphorylation and network disruption would be strongly indicative of a PP2A involvement, its affinity for PP1 being 2 orders of magnitude lower (1,2). Microcystin also behaves as a selective intracellular PP2A inhibitor by virtue of its specific binding to PP2A (42), although under cell-free conditions it is an equally potent inhibitor of PP1 (42,82).…”
Section: Table III Protective Effects Of Protein Kinase Inhibitors Agmentioning
confidence: 99%
“…As is observed for protein synthesis, autophagy is also regulated by protein phosphorylation (22,48). When protein synthesis is inhibited, it was found that inhibition of autophagic proteolysis following amino acid supplementation, was correlated with the phosphorylation of ribosomal S6 protein in hepatocytes isolated from starved rats (22).…”
Section: Figmentioning
confidence: 92%
“…Shortly after a report indicating that pharmacological inhibition of protein phosphatases inhibited autophagy in hepatocytes, 25 an important step forward occurred in our understanding of the mechanism by which amino acids inhibit autophagy. This was the discovery that adding low concentrations of amino acids (leucine being particularly effective) to hepatocytes rapidly stimulated the phosphorylation of ribosomal protein S6 (S6), in synergy with either insulin or cell swelling induced by hypo-osmosis.…”
Section: Inhibition Of Autophagy By Amino Acidsmentioning
confidence: 99%